UTILIZATION OF THE ANDROID APPLICATION SI-RAJA BUMIL (ESTIMATED FETAL WEIGHT OF PREGNANT WOMEN) IN MONITORING FETAL GROWTH IN MIDWIFE AT INDEPENDENT PREMISES IN TANJUNGPINANG CITY - Darwitri, Darwitri; Ristina Rosauli Harianja,; Metasari Sihaloho,; Kartika Sri Dewi Batubara,; Nurniati Tianastia Rullyni, (International Journal of Social Science, 2024)
Estimated fetal weight is useful for tracking fetal growth in the womb, allowing for the early detection of aberrant fetal growth. With the advancement of technology, Android users can be used as a channel for health education information. The objective of this study was to look at how utilizing the Android application Si-RAJA Bumil (Estimated Fetal Weight of Pregnant Women) affects pregnant women’s understanding of fetal growth monitoring. This study applied a quasi-experimental design with two groups pre-testing and post-testing. Samples of 60 pregnant women were collected using the Simple Random Sampling approach and divided into two groups: the intervention group and the control group. The Midwife Independent Practice in Tanjungpinang City collected data in September 2023. Wilcoxon and Mann-Whitney tests were used to analyze data. The knowledge value of pregnant women differs significantly between groups who do not utilize the Si-RAJA Bumil android application and groups that do, with a p-value of 0.003. Pregnant mothers are expected to be able to monitor their foetus’ growth and development using technological media such as the Si-RAJA Bumil application.